Climate legacies and restoration history as drivers of tallgrass prairie carbon and nitrogen cycling - Broderick, Caitlin M. (Kansas State University, 2022)
Climate change is expected to alter precipitation amounts and distributions, resulting in longer, more frequent periods of wet and dry conditions in the North American Central Plains. Grasslands in this region are often limited by water availability, so novel rainfall patterns will likely affect ecosystem functioning. The rates of two key carbon (C) fluxes, aboveground net primary productivity (ANPP) and soil respiration, are tightly linked to water availability in these grasslands. Moreover, the cycling of nitrogen (N), a co-limiting nutrient, is tied to soil moisture through microbially-mediated processes such as N mineralization, microbial immobilization, and nitrification. Decomposition unites these two cycles—controlling the rate of C sequestration and N release—and can be slowed by both droughted and saturated soils. There is a growing understanding that sufficiently long and/or intense precipitation anomalies (e.g., extended wet or dry periods) can affect ecosystem processes even after the climate event ceases, resulting in climate “legacy effects”. Tallgrass prairies, at the eastern and wetter end of the Central Plains grasslands, are both sensitive and highly resilient to short-term climate variability but the extent to which this climate sensitivity and resilience is shaped by previous climate history is largely unknown. If altered climate patterns cause changes in key ecosystem properties such as plant communities, microbial community functioning, or soil attributes, these climate changes may exert legacies on rates of prairie C and N cycling. Finally, while the relationship between climate and intact grassland ecosystem functioning has been relatively well-studied, less than five percent of North American tallgrass prairie remains intact. As a result, the persistence of tallgrass prairies and their associated ecosystem services relies heavily on the successful restoration of functioning prairies; yet future restorations will likely occur under a more hostile climate. It is therefore important to assess how climate sensitivity and resilience develops as restored prairies mature. In this dissertation, I assessed how past and current climate conditions interact to affect C fluxes, N transformations, and decomposition rates in native tallgrass prairie. I used a long-term experiment at Konza Prairie, KS, in which rainfall was supplemented by irrigation water to release tallgrass prairies from water stress for ~25 years. In 2017, I switched the irrigation and ambient treatments in a subset of plots and added new drought treatments across both historic treatments, allowing me to assess (i) how short- and long-term climate patterns differ in their effects on prairie ecosystems, (ii) whether previous climate patterns continue to shape current prairie functioning via climate legacies, and (iii) whether previous climate altered the sensitivity of prairie C and N cycling to drought conditions. In a separate project, I imposed an experimental drought across restored prairies ranging from 4 to 22 years old and measured how the sensitivity of prairie structure and function to water stress varied with restoration age. I found that a historically wetter climate increased ANPP and soil respiration on a magnitude comparable to current wet conditions, and that a history of irrigation conferred greater drought resistance to key ecosystem processes lasting up to three years. A history of irrigation also increased net N mineralization rates and nitrification rates, and microbial C/N ratios and extracellular enzyme investment suggested reduced N limitation of belowground N cycling. This legacy of increased N supply with a history of irrigation may support the higher-than-expected rates of C fluxes after ceasing irrigation. In contrast, root decomposition rates were slowest with long-term irrigation, suggesting that the increased rates of C and N mineralization may be more due to legacy effects on SOM processing than litter decay. Notably, legacy effects across response variables were most often found in lowland prairie, suggesting that topoedaphic factors are important for determining the strength of biogeochemical climate legacies. Finally, I found that restored prairie plant communities, ANPP, soil respiration, and labile N pools were surprisingly resistant to drought across all restoration ages, offering hope that restoration efforts may not be significantly hindered by future climate variability.
Keywords: Tallgrass prairie; Climate legacies; Carbon cycling; Nitrogen cycling; Restoration